MAST CELL TUMOUR IN A NON-DESCRIPT DOG - Phazanivel, N; Gopal, K; Thangathurai, R; kumar, V; Muthukrishnan, S; Manoharan, S; Balachandaran, C (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Mast cell tumours are the most frequent round cell tumour in dogs with 16-21 per cent of cutaneous tumours diagnosed (Misdrop, 2004). The most common cutaneous tumours of the dogs are mast cell tumours (Thamm and Vail, 2007). The present communication reports the occurrence of mast cell tumour in a right hind fetlock joint.